An Anatomic and Radiographic Study of the Distal Tibial Epiphysis. Issue 1 (January 2020) - Nguyen, Cynthia V.; Greene, Janelle D.; Cooperman, Daniel R.; Liu, Raymond W.
Abstract : Background: Although the undulating shape of the distal tibial epiphysis is well recognized, its anatomic features have not been well quantified in the literature. To guide the placement of surgical implants about the distal tibial physis, we investigated the topographical anatomy of the distal tibial epiphysis and explored the ability of standard radiographs to visualize the physis. Methods: We studied 30 cadaveric distal tibial epiphyses in specimens 3 to 14 years of age. Anteroposterior (AP) and lateral radiographs were obtained of each specimen and then repeated after flexible radiopaque markers were placed on the major undulations. All radiographs were analyzed to determine the height or depth of each landmark, and measurements with and without markers for each landmark were compared using intraclass correlation coefficients (ICC). In 9 specimens, similar measurements were obtained on high-resolution 3-dimensional (3D) surface scans. Results: There were 4 distinct physeal undulations usually present: an anteromedial peak (Kump's bump), a posterolateral peak, an anterior central valley, and a posterior central valley. On the 3D scans, Kump's bump averaged 5.0 mm (range, 3.0 to 6.4 mm), the posterolateral peak 2.4 mm (range, 1.2 to 5.0 mm), the anterior valley 1.3 mm (range, 0 to 3.6 mm), and the posterior valley 0.77 mm (range, 0 to 2.7 mm). Lateral radiographs with markers correlated with measurements from 3D scans better than those without markers (ICC=0.61 vs. 0.24). For AP radiographs, correlation was good to excellent regardless of marker use (ICC=0.76 vs. 0.66). Conclusions: There are 4 major undulations of the distal tibial physis. Kump's bump is the largest. A centrally placed epiphyseal screw in the medial/lateral direction or screws from anterolateral to posteromedial and anteromedial to posterolateral would tend to avoid both valleys. Particular caution should be taken when placing metaphyseal screws in the anteromedial or posterolateral distal tibia. Physeal undulations were more difficult to visualize on the lateral view. Clinical Relevance: This study provides quantitative data on the topography of the distal tibial physis to aid hardware placement. Lateral views should be interpreted with caution, as the physeal undulations are not as visible, whereas AP views can be interpreted with more confidence.